Mûsār in Prov 19:27 and Sir 6:22 - Reymond, Eric D. (Vetus Testamentum, 2025)
The difficult text of Prov 19:27 can be explained with the help of Sir 6:22, where explicit wordplay with the word מוּסָר suggests that this word was interpreted not only as the noun “instruction” from the root יסר, but also as a hophal participle from the root סור that may be translated “what is remote, obscure, rejected.”